Adjusting and doing the same: school nurses' descriptions of promoting participation in health visits with children of foreign origin - Emmie Wahlström; Marie Golsäter; Mats Granlund; Inger K. Holmström; Peter Larm; Maria Harder (BMC, 2021)
Abstract Background School nurses in the school health services are assigned to promote health and participation among children when conducting health visits. Still, for children of foreign origin this promotion of participation might be hampered by challenges related to cultural diversity and language barriers. Therefore, knowledge needs to be developed regarding how these children's participation can be promoted, to support them in sharing and describing matters important for their health. The aim was to investigate school nurses' descriptions of promoting participation for children of foreign origin in health visits. Methods A content analysis of 673 Swedish school nurses' answers to eight open-ended questions regarding promotion of participation for children of foreign origin was conducted. The open-ended questions were part of a larger web-based cross-sectional survey distributed to school nurses in Sweden. Results The results show that school nurses use three main approaches during the health visit: adjusting according to the child's proficiency in Swedish and/or cultural or national background, adjusting according to the child's individual needs, and doing the same for all children regardless of their origin. Yet, adjustments according to the child's proficiency in Swedish and/or cultural or national background were the most common. Conclusions By combining the approaches of adjusting, a child-centered care that contributes to children's participation in health visits and equity in health could be provided.